PENYELESAIAN KEWARISAN TO MANANG DALAM MASYARAKAT KECAMATAN CENRANA KABUPATEN BONE - Mustafa MH.; Habawati M.H; Dr. Jasmani M.HI (IAIN BONE, 2022)
AbstactThis article discusses the problem of the to manang inheritance system in the Bugis Bone community, with the aim of knowing the problems that occur and how to review Islamic inheritance law on these problems. This study uses a qualitative approach with observation data collection techniques and interviews in the field involving all research informants, consisting of government figures, religious leaders, heirs, and families of the heirs of Ito Manang.The results of this study indicate that, firstly, there is a problem that occurs when the heirs are misguided who are more entitled to receive a share of the property to manang, as a result, sometimes disputes occur between the heirs. second,